Laughter: demographic levels and factors, in the context of COVID-19: La risa: niveles y factores demográficos, en el contexto de la COVID-19 - Vásquez Villanueva, Salomón (2021)
Introduction: The pandemic does not stop, neither does the studies on it; This pandemic produces pain, sadness, despair and deaths, the numbers of which are incalculable. Faced with this difficult and painful situation, laughter raises its flag of hope. Objective: The study aims to describe the levels and demographic factors of laughter, in the context of COVID-19. Methods: The study corresponds to a quantitative, descriptive, cross-sectional approach. The data were obtained through a virtual survey, whose participants were 101, from the three regions. Results: Of the 101 participants, 87 (between 20 and 60 years old) are located in the high level and 14 in the medium level. Similarly, 14 (among single, married, divorced and cohabitants) in the medium level and 87 in the high level. Of the three regions (coast, mountains and jungle), 14 in the medium level and 87 in the high level. On the other hand, 6 men and 8 women are in the medium level, in the high 28 and 59, respectively. In the factor: religion, 14 (among Catholics, Adventists, Evangelicals and others) in the medium level, 87 in the high. According to the factor: educational level (primary, secondary and higher), 14 and 87 are located in the low and high level, respectively. In the family and friends circle, laughter is always experienced: 58.4% and 66.3%, respectively; for respondents it is easier to laugh, always, 54.5% and 66.3%, in the family environment and with friends, respectively. They declared that laughter prevents diseases, strengthens health, prevents covid-19, strengthens the immune system and limits the production of the hormone cortisol (responsible for stress), always 70.3%, 31.7%, 81.2; 31.7%, 71.3% and 83.2%, respectively. Conclusion: In the context of COVID-19, the most significant levels of laughter found in the study are two: medium and high; the most weighted demographic factors are: age, sex, religion, and employment status.